Low density ethylene terpolymer composition
By using polyethylene compositions with multimodal terpolymers with a density of 910 to less than 915 kg/m3, the problems of insufficient toughness and poor sealing performance in existing polyethylene compositions in heavy-duty packaging applications are solved, and a comprehensive improvement in processing performance, optical performance, toughness and sealing performance of polyethylene compositions are achieved.
Patent Information
- Application Number
- CN202380056698.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-03
- Filing Date
- 2023-08-03
- Publication Date
- 2025-04-29
Smart Images

Figure BDA0005258080650000171 
Figure BDA0005258080650000181 
Figure BDA0005258080650000182
Abstract
Description
Technical Field
[0001] The present invention relates to a polyethylene composition comprising a multimodal terpolymer of ethylene and two different comonomers, the two different comonomers being independently selected from α-olefin comonomers having 4 to 10 carbon atoms, the multimodal terpolymer having a density of 910 to less than 915 kg / m 3 The present invention also relates to a method for manufacturing the polyethylene composition, a product comprising the polyethylene composition, and the use of the polyethylene composition for manufacturing products. Background Art
[0002] Polyethylene compositions, especially those polymerized in the presence of a single site catalyst, are often used in film applications or thin wall packaging applications. Single site catalysts (eg, metallocene catalysts) produce polyethylene with a relatively narrow molecular weight distribution at high polymerization rates.
[0003] For film applications, single-site catalyzed unimodal polyethylene compositions are often used because of their good optical properties, such as low haze. However, melt processing of such polymers is not satisfactory in terms of productivity and can also lead to quality issues in the final product.
[0004] Multimodal polyethylene compositions having two or more different polyethylene components are easier to process but often have poor melt homogeneity which can lead to inhomogeneities in the final product manifested in, for example, a high gel content in the final product.
[0005] Another way to improve the processing properties of polyethylene while maintaining a narrow molecular weight distribution is to introduce long chain branches into the polymer. However, long chain branches promote directional orientation of the final product during processing, resulting in unbalanced mechanical properties, reduced impact properties, reduced tear resistance and reduced transparency, especially for films (e.g., blown films).
[0006] EP 257895A1 discloses a multimodal terpolymer of ethylene and two different comonomers, the two different comonomers being independently selected from α-olefin comonomers having 4 to 10 carbon atoms, the multimodal terpolymer being prepared in the presence of a metallocene catalyst and having a molecular weight distribution Mw / Mn of 2.0 to 5.0 and a density of 915 to 930 kg / m 3 , exhibiting good rheological properties required in membrane applications.
[0007] However, for certain heavy-duty packaging applications, such as laminated films or heavy-duty shipping bags, the terpolymers exhibit insufficient toughness, as measured by, for example, the Drop Dart Impact Strength (DDI).
[0008] Furthermore, especially for multilayer film applications, good sealing properties are beneficial.
[0009] Therefore, there is a need in the art to provide a polyethylene composition having good processability, good optical properties, high toughness and good sealing properties.
[0010] Surprisingly, it has been found that a polyethylene composition comprising a multimodal terpolymer of ethylene and two different comonomers independently selected from α-olefin comonomers having 4 to 10 carbon atoms can meet the needs of the art and exhibit an improved balance of good processability and good optical properties with high toughness and good sealing properties, the multimodal terpolymer having a density of 910 to less than 915 kg / m 3 . Summary of the invention
[0011] The present invention relates to a polyethylene composition comprising a multimodal terpolymer of ethylene and two different comonomers independently selected from α-olefin comonomers having 4 to 10 carbon atoms,
[0012] Wherein, the multimodal terpolymer comprises:
[0013] a first copolymer portion, the first copolymer portion being a copolymer of ethylene and a first comonomer, the first comonomer being 1-butene, and the comonomer content of the first comonomer in the polyethylene composition being 0.4 to 2.0 mol %, based on the total molar content of the monomer units of the polyethylene composition; and
[0014] a second copolymer portion, the second copolymer portion being a copolymer of ethylene and a second comonomer, the second comonomer being selected from α-olefin comonomers having 4 to 10 carbon atoms, the second comonomer having a different carbon atom weight than the first comonomer; and
[0015] The multimodal terpolymer has a density measured according to ISO 1183 of 910 to less than 915 kg / m 3 , preferably 911.0 to 914.5 kg / m 3 , more preferably 911.5 to 914.0 kg / m 3 ; and the polyethylene composition has a melt flow rate MFR2 measured at 190°C and 2.16kg according to ISO 1133 of 0.5 to 2.5 g / 10 min, preferably 0.6 to 2.2 g / 10 min, more preferably 0.7 to 2.0 g / 10 min.
[0016] Furthermore, the present invention also relates to a process for producing a polyethylene composition as described above or as described below, wherein the first copolymer fraction and the second copolymer fraction are both polymerized in different polymerization reactors of a multistage polymerization process in the presence of a single site catalyst.
[0017] Furthermore, the present invention also relates to an article (preferably a film) comprising the polyethylene composition as described above or below.
[0018] Finally, the present invention also relates to the use of a polyethylene composition as described above or below for the manufacture of an article, preferably a film, more preferably a monolayer film, a layer of a multilayer film for flexible packaging, a collation shrink film or a heavy-duty transport bag.
[0019] definition
[0020] A polyethylene composition according to the invention means a composition comprising more than one polymer, wherein the molar amounts of the components of the polymer composition sum to at least 50 mol-% of ethylene monomer units.
[0021] "Ethylene homopolymer" means a polymer consisting mainly of ethylene monomer units. Due to the requirements of large-scale polymerization, ethylene homopolymers may contain a small amount of comonomer units, usually less than 0.1 mol% of the ethylene homopolymer, preferably less than 0.05 mol% of the ethylene homopolymer, and most preferably less than 0.01 mol% of the ethylene homopolymer.
[0022] If a polymer is derived from ethylene monomer units and at least one α-olefin comonomer, the polymer is referred to as an "ethylene copolymer". The α-olefin comonomer is selected from α-olefin comonomers preferably having 4 to 10 carbon atoms, more preferably 4 to 6 carbon atoms. Suitable α-olefin comonomers are 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene or mixtures thereof, preferably 1-butene and 1-hexene.
[0023] If a polymer is derived from ethylene monomer units and two α-olefin comonomers having different numbers of carbon atoms, the polymer is called an "ethylene terpolymer". An ethylene terpolymer contains only units derived from ethylene and two comonomers selected from α-olefins having from 4 to 10 carbon atoms. The α-olefin comonomer is preferably selected from α-olefin comonomers having from 4 to 10 carbon atoms, more preferably from α-olefin comonomers having from 4 to 6 carbon atoms. Suitable α-olefin comonomers are 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, preferably 1-butene and 1-hexene.
[0024] The multimodal terpolymer of ethylene and two different comonomers of the present invention, said two different comonomers being independently selected from alpha-olefin comonomers having 4 to 10 carbon atoms, is hereinafter abbreviated as "multimodal ethylene terpolymer".
[0025] In the subject matter of the present invention the term "multimodal" may mean multimodal in molecular weight distribution, thus also including bimodal polymers. However, a component may also be multimodal in other properties, such as MFR or density, as specified in the detailed description of the component.
[0026] Typically, a polymer composition comprising at least two polyethylene fractions, which have been produced under different polymerisation conditions resulting in the fractions having different (weight average) molecular weights and molecular weight distributions, is termed "multimodal". The prefix "multi" relates to the number of different polymer fractions present in the polymer. Thus, for example, the term "multimodal polymer" includes so-called "bimodal" polymers consisting of two fractions. The form of the molecular weight distribution curve (i.e. the appearance of a plot of the polymer weight fraction as a function of its molecular weight) of a multimodal polymer (e.g. LLDPE) will show more than two maxima, or at least be significantly broadened compared to the curve for a single fraction.
[0027] Ideally, the molecular weight distribution curve of the multimodal polymer of the present invention shows two distinct maxima. For example, if the polymer is produced in a sequential multistage process utilizing reactors in series and using different conditions in each reactor, the polymer fractions produced in the different reactors will each have their own molecular weight distribution and weight average molecular weight. When the molecular weight distribution curve of such a polymer is recorded, the individual curves of these fractions will be superimposed on the molecular weight distribution curve of the resulting total polymer product, typically resulting in a curve with two or more distinct maxima.
[0028] By definition, in any multimodal polymer there is a lower molecular weight component (LMW) and a higher molecular weight component (HMW). The LMW component has a lower molecular weight than the higher molecular weight component. The difference is preferably at least 5000 g / mol.
[0029] For the purposes of the present invention, it is preferred that all olefins are alpha-olefins.
[0030] The "density" of a material as referred to in this specification and claims refers to the density measured according to ISO 1183.
[0031] The "melt flow rate (=MFR)" of a polymer described in the present specification and claims refers to the MFR measured according to ISO1133.
[0032] When the term "comprising" is used in the present description and claims, it does not exclude other unspecified elements of major or minor functional importance. For the purposes of the present invention, the term "consisting of" is considered to be a preferred embodiment of the term "comprising". If a group is defined hereinafter as comprising at least a certain number of embodiments, this is also to be understood as disclosing a group that preferably consists only of these embodiments.
[0033] Whenever the terms "including" or "having" are used, these terms have the same meaning as "comprising" as defined above.
[0034] When an indefinite or definite article is used when referring to a singular noun, for example "a", "an" or "the", this includes a plural of that noun unless something else is specifically stated. DETAILED DESCRIPTION
[0035] Polyethylene composition
[0036] The polyethylene composition preferably comprises the multimodal ethylene terpolymer in an amount of 85.0 to 100 wt%, more preferably 90.0 to 99.999 wt%, still more preferably 95.0 to 99.99 wt%, based on the total weight of the polyethylene composition.
[0037] The polyethylene composition may comprise other polymer resins other than the multimodal ethylene terpolymer in an amount of 0 to 15 wt.-%, based on the total weight of the polyethylene composition.
[0038] Preferably, the multimodal ethylene terpolymer is the only polymer component of the polyethylene composition. This means that the polymer component of the polyethylene composition preferably consists of the multimodal ethylene terpolymer.
[0039] The polyethylene composition may also comprise additives and / or admixtures.
[0040] The additives are preferably selected from slip agents, UV stabilizers, antioxidants, nucleating agents and mixtures thereof; preferably, based on the total weight of the polyethylene composition, the content of these additives is 0 to 5000 ppm, preferably 10 to 5000 ppm, more preferably 500 to 3000 ppm.
[0041] The admixture is preferably selected from pigments, fillers, antiblocking agents and mixtures thereof; preferably, the content of these admixtures is 0 to 5 wt %, preferably 0 to 3 wt %, more preferably 0 to 2 wt %, most preferably 0 to 1 wt %, based on the total weight of the polyethylene composition.
[0042] The additives and / or blends can be added to the polyethylene composition in the form of a masterbatch, wherein the additives and / or blends are embedded in a carrier polymer in a concentrated form to ensure better distribution of the additives and / or blends in the polyethylene composition. Where the additives and / or blends are added in the form of a masterbatch, the amount of the carrier polymer is added to the amount of the additive / or blend in the polyethylene composition, rather than to the amount of the polymer component in the polyethylene composition.
[0043] The polyethylene composition preferably comprises ethylene monomer units and comonomer units selected from two different comonomers independently selected from α-olefins having 4 to 10 carbon atoms.
[0044] The two different comonomers are preferably selected from 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, more preferably from 1-butene, 1-hexene and 1-octene, still more preferably from 1-butene and 1-hexene.
[0045] Preferably, the polymer units present in the polyethylene composition consist of ethylene monomer units and comonomer units selected from two different comonomers independently selected from α-olefins having from 4 to 10 carbon atoms.
[0046] The first comonomer is 1-butene.
[0047] The second comonomer is preferably selected from 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, more preferably selected from 1-butene, 1-hexene and 1-octene, still more preferably selected from 1-hexene.
[0048] Preferably, the total content of comonomers in the polyethylene composition is from 2.4 to 6.0 mol%, preferably from 2.7 to 5.0 mol%, more preferably from 3.0 to 4.5 mol%.
[0049] The comonomer content of the first comonomer in the polyethylene composition (ie, 1-butene content) is 0.4 to 2.0 mol%, preferably 0.5 to 1.5 mol%, more preferably 0.6 to 1.2 mol%, based on the total molar content of monomer units in the polyethylene composition.
[0050] In addition, preferably, based on the total molar content of the monomer units of the polyethylene composition, the comonomer content of the second comonomer in the polyethylene composition (preferably 1-hexene content) is 2.0 to 4.0 mol%, preferably 2.2 to 3.5 mol%, more preferably 2.4 to 3.3 mol%.
[0051] The polyethylene composition has a melt flow rate MFR2 measured according to ISO 1133 at 190°C and 2.16 kg of 0.5 to 2.5 g / 10 min, preferably 0.6 to 2.2 g / 10 min, more preferably 0.7 to 2.0 g / 10 min.
[0052] Furthermore, the polyethylene composition has a melt flow rate MFR5 measured according to ISO 1133 at 190° C. and 5 kg of 1.5 to 7.0 g / 10 min, preferably 1.7 to 6.0 g / 10 min, more preferably 2.0 to 5.0 g / 10 min.
[0053] In addition, the melt flow rate MFR of the polyethylene composition measured according to ISO 1133 at 190°C and 21.6 kg is 21 It is preferably 10.0 to 35.0 g / 10 min, more preferably 12.5 to 32.5 g / 10 min, still more preferably 15.0 to 30.0 g / 10 min.
[0054] In addition, the flow rate ratio FRR of the polyethylene composition 21 / 2 (i.e. MFR 21 The ratio of MFR to MFR2) is preferably from 15.0 to 25.0, more preferably from 16.5 to 23.5, still more preferably from 17.5 to 22.5.
[0055] In addition, the flow rate ratio FRR of the polyethylene composition 21 / 5 (i.e. MFR 21 The ratio of MFR to MFR5) is preferably from 4.5 to 10.0, more preferably from 5.5 to 9.0, still more preferably from 6.0 to 8.0.
[0056] Furthermore, the polydispersity index of the polyethylene composition (ie, the ratio of the weight average molecular weight to the number average molecular weight, Mw / Mn) is preferably from 2.0 to 6.0, more preferably from 2.5 to 5.5.
[0057] Furthermore, the melting temperature of the polyethylene composition as determined by DSC measurement is preferably from 120 to 130°C, more preferably from 123 to 128°C.
[0058] Furthermore, the polyethylene composition preferably has a melting enthalpy determined by DSC measurement of 100 to 115 J / g, more preferably 103 to 110 J / g.
[0059] Furthermore, the polyethylene composition preferably has a crystallinity determined by DSC measurement of 30 to 40%, more preferably 35 to 38%.
[0060] The polyethylene composition preferably has a molecular structure comprising fractions of different lamellar thicknesses. The thickness of the different lamellar fractions can be measured by a continuous self-nucleation and annealing thermal fractionation (SSA) technique, which can be run on a differential scanning calorimeter (DSC), as described in the Measurement Methods section below.
[0061] The SSA technique involves sequential self-nucleation and annealing steps on a polymer sample. After thermal conditioning (multiple heating and cooling cycles), the final DSC heating run reveals the melting temperature distribution caused by the SSA thermal treatment, which is caused by the heterogeneity of the chain structure of the analyzed polymer. The SSA technique is particularly suitable for studying the extent and distribution of short chain branches produced by the copolymerization of ethylene with α-olefins.
[0062] Preferably, the amount of the lamellar fraction having a lamellar thickness of more than 11.8 nm to 21.7 nm is 5.0 to 25.0%, more preferably 7.5 to 22.5%, still more preferably 10.0 to 20.0%, based on the total amount of the lamellar fraction.
[0063] Further preferably, the amount of the lamellar fraction having a lamellar thickness of more than 8.1 nm to 11.8 nm is 17.5 to 40.0%, more preferably 20.0 to 37.5%, still more preferably 22.5 to 35.0%, based on the total amount of the lamellar fraction.
[0064] Furthermore, the amount of the lamellar fraction having a lamellar thickness of more than 6.1 nm to 8.1 nm is 12.5 to 30.0%, more preferably 15.0 to 27.5%, still more preferably 17.5 to 25.0%, based on the total amount of the lamellar fraction.
[0065] Furthermore, the amount of the lamellar fraction having a lamellar thickness of 0 nm to 6.1 nm is preferably 30.0 to 50.0%, more preferably 32.5 to 47.5%, still more preferably 35.0 to 45.0%, based on the total amount of the lamellar fraction.
[0066] The amounts of fractions with different lamellar thicknesses are given in weight % (wt %).
[0067] Ethylene terpolymers are terpolymers of ethylene and two different comonomers independently selected from alpha-olefins having from 4 to 10 carbon atoms.
[0068] The two different comonomers are preferably selected from 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, more preferably from 1-butene, 1-hexene and 1-octene, still more preferably from 1-butene and 1-hexene.
[0069] Preferably, the total comonomer content of the ethylene terpolymer is from 2.4 to 6.0 mol%, preferably from 2.7 to 5.0 mol%, more preferably from 3.0 to 4.5 mol%.
[0070] The ethylene terpolymer comprises: a first copolymer portion, which is a copolymer of ethylene and a first comonomer (1-butene); and a second copolymer portion, which is a copolymer of ethylene and a second comonomer, wherein the second comonomer is selected from α-olefin comonomers having 4 to 10 carbon atoms; wherein the first comonomer and the second comonomer have different numbers of carbon atoms.
[0071] The first comonomer is 1-butene.
[0072] The second comonomer is preferably selected from 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, more preferably selected from 1-butene, 1-hexene and 1-octene, still more preferably selected from 1-hexene.
[0073] Based on the total molar content of the monomer units of the ethylene terpolymer, the comonomer content of the first comonomer in the ethylene terpolymer (i.e., 1-butene content) is 0.4 to 2.0 mol%, preferably 0.5 to 1.5 mol%, and more preferably 0.6 to 1.2 mol%.
[0074] Furthermore, preferably, the comonomer content of the second comonomer in the ethylene terpolymer (preferably 1-hexene content) is 2.0 to 4.0 mol%, preferably 2.2 to 3.5 mol%, more preferably 2.4 to 3.3 mol%, based on the total molar content of the monomer units of the ethylene terpolymer.
[0075] Ethylene terpolymers are multimodal in terms of comonomer content, since the two ethylene copolymer parts have different numbers of carbon atoms in the comonomer.
[0076] The first copolymer portion is preferably a copolymer of ethylene and 1-butene comonomer and the second copolymer portion is preferably a copolymer of ethylene and 1-hexene.
[0077] The content of the first copolymer part in the ethylene terpolymer is preferably 35 to 55 wt%, more preferably 37 to 52 wt%, still more preferably 40 to 50 wt%, based on the total weight of the ethylene terpolymer.
[0078] The density of the first copolymer part measured according to ISO 1183 is preferably from 920.0 to 930.0 kg / m 3 , more preferably 925.0 to 928.0 kg / m 3 .
[0079] Furthermore, the first copolymer part preferably has a melt flow rate MFR2 measured at 190° C. and 2.16 kg according to ISO 1133 of 1.0 to 5.0 g / 10 min, more preferably 1.5 to 3.5 g / 10 min.
[0080] The content of the second copolymer part in the ethylene terpolymer is preferably 65 to 45 wt%, more preferably 63 to 48 wt%, still more preferably 60 to 50 wt%, based on the total weight of the ethylene terpolymer.
[0081] The weight ratio of the first copolymer part to the second copolymer part in the ethylene terpolymer is preferably from 35:65 to 55:45, more preferably from 37:63 to 52:48, still more preferably from 40:60 to 50:50.
[0082] The density of the second copolymer part is preferably 890.0 to 910.0 kg / m 3 , more preferably 895.0 to 905.0 kg / m 3 .
[0083] Furthermore, the melt flow rate MFR2 of the second copolymer part is preferably from 0.01 to 10.0 g / 10 min, more preferably from 0.1 to 1.5 g / 10 min.
[0084] When manufactured using a multistage process, where the second copolymer fraction is polymerized in a subsequent polymerization stage and cannot be measured directly, the density and MFR2 of the second copolymer fraction can be calculated according to the formulas described in the determination methods in the Examples section below.
[0085] The density of the ethylene terpolymer measured according to ISO 1183 is 910 to less than 915 kg / m 3 , preferably 911.0 to 914.5 kg / m 3 , more preferably 911.5 to 914.0 kg / m 3 .
[0086] The melt flow rate MFR2 of the ethylene terpolymer, measured according to ISO 1133 at 190° C. and 2.16 kg, is preferably from 0.5 to 2.5 g / 10 min, more preferably from 0.6 to 2.2 g / 10 min, still more preferably from 0.7 to 2.0 g / 10 min.
[0087] Furthermore, the ethylene terpolymer has a melt flow rate MFR5 measured at 190° C. and 5 kg according to ISO 1133, preferably 1.5 to 7.0 g / 10 min, more preferably 1.7 to 6.0 g / 10 min, still more preferably 2.0 to 5.0 g / 10 min.
[0088] In addition, the melt flow rate MFR of the polyethylene composition measured according to ISO 1133 at 190°C and 21.6 kg is 21 It is preferably 10.0 to 35.0 g / 10 min, more preferably 12.5 to 32.5 g / 10 min, still more preferably 15.0 to 30.0 g / 10 min.
[0089] The ethylene terpolymer is preferably obtainable by polymerization in the presence of a single site catalyst system. The single site catalyst system preferably comprises a catalytically active metallocene compound or complex in combination with a cocatalyst.
[0090] method
[0091] Furthermore, the present invention relates to a process for producing a polyethylene composition as described above or as described below, wherein the first copolymer fraction and the second copolymer fraction are both polymerized in different polymerization reactors of a multistage polymerization process in the presence of a single site catalyst.
[0092] Preferably, all embodiments and properties of the polyethylene composition as described above or below are applicable to the process of the present invention.
[0093] The single site catalyst preferably comprises a catalytically active metallocene compound or complex in combination with a cocatalyst.The metallocene compound or complex is also referred to herein as an organometallic compound (C).
[0094] The organometallic compound (C) comprises a transition metal (M) from Groups 3 to 10 of the Periodic Table of Elements (IUPAC 2007) or an actinide or lanthanide.
[0095] According to the present invention, the term "organometallic compound (C)" includes any metallocene compound of a transition metal, which carries at least one organic (coordinating) ligand and exhibits catalytic activity alone or together with a cocatalyst. Transition metal compounds are well known in the art and preferably include metal compounds of Groups 3 to 10 (e.g. Groups 3 to 7 or Groups 3 to 6, e.g. Groups 4 to 6) of the Periodic Table of the Elements (IUPAC 2007) and lanthanides or actinides.
[0096] In one embodiment, the organometallic compound (C) has the following formula (I):
[0097] (L) m R n MX q (I)
[0098] In the formula
[0099] "M" is a transition metal (M) of Groups 3 to 10 of the Periodic Table of the Elements (IUPAC 2007),
[0100] Each "X" is independently a monoanionic ligand, such as an o-ligand,
[0101] Each "L" is independently an organic ligand coordinated to the transition metal "M",
[0102] "R" is a bridging group connecting the organic ligand (L),
[0103] "m" is 1, 2 or 3, preferably 2,
[0104] "n" is 0, 1 or 2, preferably 1,
[0105] "q" is 1, 2 or 3, preferably 2, and
[0106] m+q equals the valence of the transition metal (M).
[0107] “M” is preferably selected from zirconium (Zr), hafnium (Hf) or titanium (Ti), and more preferably selected from zirconium (Zr) and hafnium (Hf).
[0108] "X" is preferably halogen, most preferably Cl.
[0109] Most preferably, the organometallic compound (C) is a metallocene complex, which includes a transition metal compound as defined above, which contains a cyclopentadienyl, indenyl or fluorenyl ligand as a substituent "L". In addition, the ligand "L" may have a substituent, such as an alkyl, aryl, aralkyl, alkaryl, silyl, silyloxy, alkoxy or other heteroatom groups, etc. Suitable metallocene catalysts are known in the art and are disclosed in, inter alia, WO-A-95 / 12622, WO-A-96 / 32423, WO-A-97 / 28170, WO-A-98 / 32776, WO-A-99 / 61489, WO-A-03 / 010208, WO-A-03 / 051934, WO-A-03 / 051514, WO-A-2004 / 085499, EP-A-1752462 and EP-A-1739103.
[0110] Most preferably, the metallocene catalyst (i.e. the catalytically active metallocene complex as defined above) is used together with a cocatalyst (also referred to as an activator). Suitable activators are metal alkyl compounds known in the art, especially aluminum alkyl compounds. Particularly suitable activators for use with metallocene catalysts are alkylaluminum oxide compounds, such as methylaluminoxane (MAO), tetraisobutylaluminoxane (TIBAO) or hexaisobutylaluminoxane (HIBAO).
[0111] The first and second copolymer parts of the ethylene terpolymer may be produced by any suitable polymerization process known in the art comprising at least two polymerization reactors, wherein the polymerization is generally carried out in solution, slurry, bulk or gas phase.
[0112] The first copolymer part is preferably manufactured in a first polymerization reactor, and the second copolymer part is preferably manufactured in a second polymerization reactor. The first polymerization reactor and the second polymerization reactor can be connected in any order, that is, the first polymerization reactor can be located before the second reactor, or the second polymerization reactor can be located before the first polymerization reactor, or, the polymerization reactors can be connected in parallel. However, it is preferred to operate the polymerization reactor in a cascade mode. The polymerization reactor can be operated under slurry, solution or gas phase conditions or a combination thereof.
[0113] Suitable processes involving cascaded slurry and gas phase polymerisation reactors are disclosed inter alia in WO-A-92 / 12182 and WO-A-96 / 18662.
[0114] It is generally preferred to remove the reactants from the polymer from the previous polymerization reactor before introducing the polymer into the subsequent polymerization reactor. This is preferably done when transferring the polymer from one polymerization reactor to another.
[0115] The catalyst may be transferred to the polymerization reactor by any method known in the art. For example, the catalyst may be suspended in a diluent and maintained as a homogeneous slurry, the catalyst may be mixed with a viscous mixture of grease and oil and the resulting paste may be fed to the polymerization reactor, or the catalyst may be allowed to settle and portions of the catalyst slurry thus obtained may be introduced into the polymerization reactor.
[0116] The polymerization in the first polymerization reactor is preferably carried out in slurry. The polymer particles formed in the polymerization are then suspended in a fluid hydrocarbon together with the catalyst broken up and dispersed in the particles. The slurry is stirred to transfer the reactants from the fluid to the particles.
[0117] The polymerization is usually carried out in an inert diluent, which is usually a hydrocarbon diluent, such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or a mixture thereof. The preferred diluent is a low-boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of such hydrocarbons, and the preferred diluent is propane.
[0118] The ethylene content of the slurry fluid phase may be from 2 to about 50 mol%, preferably from about 2 to about 20 mol%, especially from about 3 to about 12 mol%.
[0119] The temperature of the slurry polymerization is generally from 50 to 115° C., preferably from 60 to 110° C., in particular from 70 to 100° C.; the pressure is from 1 to 150 bar, preferably from 10 to 100 bar.
[0120] The slurry polymerization can be carried out in any reactor known for slurry polymerization.
[0121] Such reactors include continuous stirred tank reactors and loop reactors. It is particularly preferred to polymerize in a loop reactor. In such reactors, the slurry is circulated at high speed along a closed pipeline by a circulating pump. Loop reactors are well known in the art, for example, in US-A-4582816, US-A-3405109, US-A-3324093, EP-A-479186 and US-A-5391654.
[0122] Sometimes it is advantageous to carry out slurry polymerization above the critical temperature and pressure of the fluid mixture. Such operation is described in US-A-5391654. In such operation, the temperature is generally 80 to 110°C, preferably 85 to 105°C, and the pressure is 30 to 150 bar, preferably 50 to 100 bar.
[0123] The slurry may be withdrawn from the reactor continuously or intermittently. A preferred mode of intermittent withdrawal is to use settling legs, wherein the slurry is allowed to concentrate and then a batch of concentrated slurry is withdrawn from the reactor. It is advantageous to combine the continuous withdrawal with a suitable concentration method, such as disclosed in EP-A-1310295 and EP-A-1591460.
[0124] As is known in the art, hydrogen can be fed into the reactor to control the molecular weight of the polymer. In addition, it is preferred that a comonomer selected from alpha-olefins of 4 to 10 carbon atoms (e.g., 1-butene) is added to the reactor, for example, to control the density of the polymer product. The actual feed amount of such hydrogen and comonomer depends on the catalyst used and the desired melt index (or molecular weight) and density (or comonomer content) of the resulting polymer.
[0125] The polymerization in the second polymerization reactor is preferably carried out in gas phase, preferably in a fluidized bed reactor, a fast fluidized bed reactor or a settling bed reactor or any combination of these reactors. The polymerization in the second polymerization zone is more preferably carried out in a fluidized bed gas phase reactor, wherein ethylene is polymerized in an upwardly moving gas stream together with a comonomer selected from α-olefins having 4 to 10 carbon atoms (e.g. 1-hexene) in the presence of a polymerization catalyst (preferably in the presence of a reaction mixture from the first polymerization reactor). The reactor typically comprises a fluidized bed comprising growing polymer particles containing an active catalyst located above a fluidizing grid.
[0126] The polymer bed is fluidized with the help of a fluidizing gas, which contains olefin monomers, possible comonomers, possible chain growth controllers or chain transfer agents (e.g. hydrogen) and possible inert gases. The fluidizing gas is introduced into an inlet chamber at the bottom of the reactor. One or more of the above components may be added continuously to the fluidizing gas to compensate for losses caused by the reaction or product extraction, etc.
[0127] The fluidizing gas passes through the fluidized bed. The superficial velocity of the fluidizing gas must be higher than the minimum fluidizing velocity of the particles contained in the fluidized bed, otherwise no fluidization will occur. On the other hand, the velocity of the gas should be lower than the starting velocity for pneumatic transport, otherwise the entire bed will be entrained with the fluidizing gas.
[0128] When the fluidizing gas contacts the bed containing the active catalyst, the reactive components in the gas (such as monomers and chain transfer agents) react in the presence of the catalyst to form polymer products. At the same time, the gas is heated by the heat of reaction.
[0129] The unreacted fluidizing gas is discharged from the top of the reactor and cooled in a heat exchanger to remove the heat of reaction. The gas is cooled to a temperature below the bed temperature to prevent the bed from heating up due to the reaction. The gas can be cooled to a temperature at which part of the gas condenses. When the droplets enter the reaction zone, they are evaporated.
[0130] The heat of evaporation then helps remove the heat of reaction. This operation is known as condensing mode, and variations of this mode are disclosed in WO-A-2007 / 025640, USA-4543399, EP-A-699213 and WO-A-94 / 25495, among others.
[0131] It is also possible to add condensing agents to the recycle gas stream, as disclosed in EP-A-696 293. Condensing agents are non-polymerizable components, such as n-pentane, isopentane, n-butane or isobutane, which are at least partially condensed in the cooler.
[0132] The gas is then compressed and recycled to the inlet chamber of the reactor. Fresh reactants are introduced into the fluidizing gas stream before entering the reactor to compensate for losses caused by the reaction and product extraction. As is known, the composition of the fluidizing gas is analyzed and gas components are introduced to keep the composition constant. The actual composition is determined by the desired characteristics of the product and the catalyst used in the polymerization.
[0133] The catalyst can be introduced into the reactor continuously or intermittently in various ways. When the gas phase reactor is part of a reactor cascade, the catalyst is usually dispersed in the polymer particles from the previous polymerization stage. As disclosed in EP-A-1415999 and WO-A-00 / 26258, the polymer particles can be introduced into the gas phase reactor. In particular, if the previous reactor is a slurry reactor, it is advantageous to feed the slurry directly into the fluidized bed of the gas phase reactor, as disclosed in EP-A-887379, EP-A-887380, EP-A-887381 and EP-A-991684.
[0134] The polymer product can be taken out from the gas phase reactor continuously or intermittently, or a combination of these methods can be used. WO-A-00 / 29452 and the like disclose continuous taking out, and US-A-4621952, EP-A-188125, EP-A-250169 and EP-A-579426 and the like disclose intermittent taking out.
[0135] If desired, electrostatic agents (such as water, ketones, aldehydes and alcohols) may also be introduced into the gas phase reactor. The reactor may also include a mechanical agitator to further promote mixing within the fluidized bed.
[0136] Typically, the fluidized bed polymerisation reactor is operated at a temperature of from 50 to 100° C., preferably from 65 to 90° C. The pressure is suitably from 10 to 40 bar, preferably from 15 to 30 bar.
[0137] A prepolymerization step may be performed before the polymerization of the first copolymer portion and the second copolymer portion in the first and second polymerization reactors. The purpose of the prepolymerization is to polymerize a small amount of polymer onto the catalyst at low temperature and / or low monomer concentration. By prepolymerization, the performance of the catalyst in the slurry can be improved and / or the properties of the final polymer can be changed.
[0138] The prepolymerization step can be carried out in slurry or in gas phase. The prepolymerization is preferably carried out in slurry, preferably in a loop reactor. The prepolymerization is then preferably carried out in an inert diluent, preferably a low boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of such hydrocarbons.
[0139] The temperature in the prepolymerization step is usually from 0 to 90°C, preferably from 20 to 80°C, more preferably from 25 to 70°C.
[0140] The pressure is not critical and is generally from 1 to 150 bar, preferably from 10 to 100 bar.
[0141] The catalyst components are preferably all introduced into the prepolymerization step.
[0142] Preferably, the reaction product of the prepolymerization step is then introduced into the first polymerization reactor.
[0143] The method for producing the polyethylene composition preferably comprises the following polymerization steps:
[0144] a) polymerizing ethylene and a first comonomer in the presence of a single site catalyst in a first polymerization reactor to obtain a first reaction mixture comprising a first copolymer portion and the single site catalyst;
[0145] b) transferring the first reaction mixture from the first polymerization reactor to a second polymerization reactor;
[0146] c) polymerizing ethylene and a second comonomer in the presence of the single site catalyst and the first copolymer fraction in a second polymerization reactor to obtain a second reaction mixture comprising the first copolymer fraction, the second copolymer fraction, and the single site catalyst;
[0147] d) removing the second reaction mixture from the second polymerization reactor; and
[0148] e) compounding the second reaction mixture to obtain a polyethylene composition.
[0149] The first polymerisation reactor is preferably a bulk reactor operated as described above.
[0150] The second polymerisation reactor is preferably a gas phase reactor operated as described above.
[0151] The first comonomer is preferably 1-butene.
[0152] The second comonomer is preferably 1-hexene.
[0153] The molar ratio of the first comonomer to ethylene for the polymerization of the first copolymer portion is preferably greater than 110 to 350 mol / kmol, more preferably 125 to 300 mol / kmol, still more preferably 150 to 275 mol / kmol.
[0154] Furthermore, the molar ratio of the second comonomer to ethylene for polymerization of the second copolymer portion is preferably 15 mol / kmol to less than 41 mol / kmol, more preferably 17 mol / kmol to 40 mol / kmol, still more preferably 20 to 30 mol / kmol.
[0155] The ratio of hydrogen to ethylene for the polymerization of the first copolymer portion is preferably greater than 0.05 mol / kmol to 1.0 mol / kmol, preferably 0.10 mol / kmol to 0.50 mol / kmol, more preferably 0.15 to 0.35 mol / kmol.
[0156] The ratio of hydrogen to ethylene for the polymerization of the second copolymer fraction is preferably greater than 0.01 mol / kmol to 0.75 mol / kmol, preferably in the range of 0.05 to 0.30 mol / kmol, more preferably 0.10 to 0.25 mol / kmol.
[0157] The ethylene terpolymer obtained from the polymerization stage as described above is then usually extruded and made into particles. Extrusion can be carried out in a twin screw extruder in a manner known in the art. An example of a suitable twin screw extruder is a co-rotating twin screw extruder. These extruders are manufactured by Copernion or Japan Steel Works, etc. Another example is a counter-rotating twin screw extruder. Such extruders are manufactured by Kobe Steel, Ltd. or Japan Steel Works, etc. Before extrusion, at least a portion of the above-mentioned required additives is preferably mixed with the ethylene terpolymer. The extruder generally includes a melting section for melting the ethylene terpolymer and a mixing section for homogenizing the ethylene terpolymer melt. Melting and homogenization are achieved by introducing energy into the ethylene terpolymer. Suitable specific energy input (SEI) levels are from about 150 to about 450 kWh / ton of ethylene terpolymer, preferably from 175 to 350 kWh / ton of ethylene terpolymer.
[0158] Products
[0159] Furthermore, the present invention relates to an article, preferably a film, comprising the polyethylene composition as described above or below.
[0160] Preferably, all embodiments and properties of the polyethylene composition and the method for making the polyethylene composition as described above or below are applicable to the article of the invention.
[0161] The article may be a monolayer film, a layer of a multilayer film for flexible packaging, a layer of a collation shrink film, or a layer of a heavy duty shipping bag.
[0162] The terms "single-layer film" and "multi-layer film" have well-known meanings in the art.
[0163] The layer of monolayer film or multilayer film or bag can be made up of the polyethylene composition comprising ethylene terpolymer and optional additive, or be made up of the mixture of polyethylene composition and other polymers.In the case of being made up of mixture, any other polymer is all different from ethylene terpolymer, is preferably polyolefin.In the film preparation process, a part of the above-mentioned additive (such as processing aid) can be optionally added to the polymer composition.Preferably, the layer comprises at least 50 % by weight, preferably at least 60 % by weight, preferably at least 70 % by weight, more preferably at least 80 % by weight of the polyethylene composition of the present invention.More preferably, the layer of film of the present invention is made up of polyethylene composition.
[0164] Thus, the film or bag may comprise a single layer (ie a monolayer) or be multilayer. A multilayer film or bag generally preferably comprises at least 3 layers.
[0165] The film is produced by any conventional film extrusion process known in the art to be suitable for producing blown or cast films.
[0166] Blown films are typically made by extrusion through an annular die, blown into a tubular film by forming bubbles which, after solidification, burst between nip rolls. The film can then be cut, trimmed or converted (e.g., gusseted) as desired. Conventional film making techniques can be used in this regard. If the preferred blown film is a multilayer film, the layers are typically coextruded. The skilled person is aware of suitable extrusion conditions.
[0167] Cast films are typically made by extrusion through a slot die, passing through water-cooled rollers and winding. Conventional film making techniques can be used in this regard. If the preferred cast film is a multilayer film, the layers are typically coextruded. The skilled person is aware of suitable extrusion conditions.
[0168] The film or bag is preferably a blown film.
[0169] The resulting film or bag can have any thickness conventional in the art. The thickness of the film is not important and depends on the end use. Therefore, the thickness of the film can be, for example, less than 300 μm, typically 6 to 200 μm, preferably 10 to 180 μm, for example 20 to 150 μm or 20 to 120 μm. If desired, the polyethylene composition of the present invention can be made to have a thickness of less than 100 μm, for example less than 50 μm. It is also possible to manufacture blown films with a thickness of even less than 20 μm while maintaining good mechanical properties.
[0170] The article is preferably a film having one or more of the following characteristics, preferably all of them:
[0171] The dart impact force (DDI) measured according to BICM90728 on a single-layer blown film with a thickness of 40 μm is at least 1000 g, preferably at least 1100 g, more preferably at least 1200 g, and / or the upper limit is preferably not more than 2000 g; and / or
[0172] The hot stick temperature at 1 N maximum force measured according to BICM90720 on a single-layer blown film with a thickness of 40 μm is 65 to 90°C, preferably 70 to 88°C, more preferably 75 to 85°C; and / or
[0173] The gloss at 60°C, measured according to ISO 2813 on a monolayer blown film having a thickness of 40 μm, is 20 to 50.
[0174] use
[0175] Finally, the present invention relates to the use of a polyethylene composition as described above or below for the manufacture of an article, preferably a film, more preferably a monolayer film, a layer of a multilayer film for flexible packaging, a collation shrink film or a heavy duty transport bag.
[0176] Preferably, all embodiments and characteristics of the polyethylene composition, the method for producing the polyethylene composition and the article as described above or below are applicable to the use according to the present invention.
[0177] The invention will now be described with reference to the following non-limiting examples.
[0178] Example
[0179] 1. Determination method
[0180] Melt flow rate
[0181] The melt flow rate (MFR) is measured according to ISO 1133 and is reported in g / 10 min. The MFR indicates the flowability and therefore the processability of a polymer. The higher the melt flow rate of a polymer, the lower the viscosity.
[0182] The MFR2 of polyethylene is measured at a temperature of 190°C and a load of 2.16 kg.
[0183] The MFR5 of polyethylene is measured at a temperature of 190°C and a load of 5 kg.
[0184] MFR of polyethylene 21 The measurement was performed at a temperature of 190° C. and a load of 21.6 kg.
[0185] The MFR2 of the second ethylene copolymer fraction polymerized in the second polymerization reactor is calculated from the MFR2 of the first ethylene copolymer fraction polymerized in the first polymerization reactor and the MFR2 of the ethylene terpolymer as follows:
[0186] LogMFR 最终 = weight % 第一 ×LogMFR 第一 +Weight% 第二 ×LogMFR 第二
[0187] In the formula
[0188] - "final" means "ethylene terpolymer";
[0189] - "first" means "the first ethylene copolymer fraction produced in the first reactor";
[0190] - "Table 2" represents the "second ethylene copolymer fraction produced in the second reactor".
[0191] density
[0192] The density of the polymer was measured according to ISO 1183-1:2004 Method A on compression molded specimens prepared according to EN ISO 1872-2 (February 2007) and is expressed in kg / m 3 .
[0193] The density of the second ethylene copolymer part polymerized in the second polymerization reactor is calculated from the density of the first ethylene copolymer part polymerized in the first polymerization reactor and the density of the ethylene terpolymer as follows:
[0194] Density second = (density final – weight % first x density first) / weight % second
[0195] In the formula
[0196] "Final" means "ethylene terpolymer";
[0197] "first" means "the first ethylene copolymer portion produced in the first reactor";
[0198] "Second" means "a second ethylene copolymer portion produced in a second reactor".
[0199] Comonomer content
[0200] 13C-NMR spectra of samples dissolved in 1,2,4-trichlorobenzene / benzene-d6 (90 / 10 w / w) were recorded by a Bruker 400 MHz spectrometer at 130° C. Conversion between % wt and % mol can be performed by calculation.
[0201] DSC analysis
[0202] Melting temperature Tm and crystallization temperature Tc are measured on 5 to 7 mg samples using a TA Instrument Q2000 differential scanning calorimeter (DSC). DSC is performed in accordance with ISO 11357 / Part 3 / Method C2 in a heating / cooling / heating cycle with a scanning rate of 10°C / min and a temperature range of 25 to +225°C. The crystallization temperature is determined by the cooling step, the melting temperature (Tm) and the melting enthalpy (Hm) are determined by the second heating step.
[0203] Layer thickness
[0204] The continuous self-nucleation / annealing (SSA) technique amplifies the micro-effects by annealing the unmelted crystals at each stage of the process, thereby enhancing the potential molecular fractionation that may occur during the crystallization process. General references and other information can be found in the review article by Müller and Arnal [AJ Müller, ML Arnal, Thermal fractionation of polymers, Prog. Polym. Sci. 30 (2005) 559–603]. SSA is carried out on a TA Instruments Q2000 differential scanning calorimeter equipped with an RCS90 cooling system and calibrated by indium and tin. 5-10 mg samples from compression molded sheets are used. All samples are packaged in Tzero aluminum pans. Ultra-high purity dry nitrogen is used as an inert gas. The experimental scheme is as follows:
[0205] (a) The previous thermal history was eliminated by heating the sample from room temperature to 180 °C at a rate of 20 °C / min and holding isothermally for 5 min.
[0206] (b) In this method, 8 subsequent cooling / heating cycles were used at a rate of 10°C / min, and the first isothermal crystallization temperature was selected to be 126°C. The duration of each isothermal crystallization step was 5 minutes. After each isothermal crystallization step, the sample was cooled to 30°C and kept isothermal for 5 minutes.
[0207] (c) The subsequent isothermal temperature was always kept 5 °C lower than the previous step, i.e., the sample was heated from 30 °C to the second isothermal crystallization temperature of 121 °C.
[0208] (d) After the final isothermal crystallization step at 91 °C, the sample was cooled to 0 °C and the cooled sample was heated to 180 °C at a heating rate of 10 °C / 10 min to obtain the melting curve.
[0209] The last heating run after SSA treatment shows a series of melting peaks that correspond to the number of SSA cycles in which annealing was promoted. The Gibbs-Thompson equation can then be used to establish a correlation between melting temperature and lamellar thickness:
[0210]
[0211] In the formula, is the equilibrium melting point of an infinitely thick crystal, σ e is the specific surface energy, is the melting enthalpy per unit mass, L c is the layer thickness, T m is the melting temperature of the sheet. σ e and Take 415K, 93×10 -3 J / m 3 and 3×10 8 J / m 3 [L. Mandelkern, RG Lamo, Thermodynamic quantities governing melting, in Phys. Prop. Polym. Handb., Springer, 2007: pp. 165–186. ].
[0212] The melting enthalpy is determined from the quotient of the heat flow of the sample between the inferred start and end of melting and the initial weight as described in ISO 11357-3. The melting curves are quantified using the definite integration method (with a step size of 10°C) to determine the lamellar thickness distribution.
[0213] Drop Dart Impact (DDI)
[0214] DDI is measured according to ISO 7765-1 Method A (alternative test technique) on blown films (prepared as described in the Examples section below) having a thickness of 40 μm. A dart with a hemispherical head of 38 mm in diameter is dropped from a height of 0.66 m onto the film clamped over an orifice. Twenty groups of specimens are tested consecutively. One weight is used for each group, and the weight is increased (or decreased) from one group to another in uniform increments. The weight that causes 50% of the specimens to break is calculated and reported.
[0215] Hot tack
[0216] Hot tack was measured on a DTC according to ASTM F 1921 under the following conditions: 3 bar, sealing time 1 s, cooling time 0.1 s (release), 2 Teflon jaws, hot tack 1 N, peel speed 200 mm / s, sealing pressure 0.25 N / mm 2 , dwell / seal time 1 s, delay time 100 ms; test / peel speed 200 mm / s; flat jaws covered with Teflon tape.
[0217] Optical properties
[0218] Gloss was measured according to DIN 67530 / ISO 2813 at an angle of 60° on monolayer blown films with a thickness of 40 μm, produced as described in the Examples section below. Gloss values are recorded and reported in Gloss Units (GU).
[0219] 2. Polyethylene ingredients
[0220] The catalyst used to prepare the ethylene terpolymers of Examples IE1-IE3 and CE1-CE4 was a metallocene catalyst, wherein the metallocene complex bis(1-methyl-3-n-butylcyclopentadienyl)Zr(IV)Cl2 (CAS No. 151840-68-5) was supported on Albemarle On the carrier.
[0221] The polymerization of the ethylene terpolymers of Examples IE1-IE3 and CE1-CE4 was carried out at The process is carried out in an apparatus comprising a prepolymerization loop reactor, a loop reactor and a gas phase reactor, wherein the slurry in the prepolymerization reactor is intermittently withdrawn and introduced into the loop reactor, and subsequently the slurry is intermittently withdrawn from the loop reactor by using settling legs and fed into a flash tank having a temperature of 50°C and a pressure of 3 bar, from where the polymer is fed into a gas phase reactor (GPR).
[0222] The polymerization conditions are listed in Table 1 below.
[0223] Table 1: Polymerization conditions of ethylene terpolymers of IE1-IE3 and CE1-CE4
[0224]
[0225]
[0226]
[0227] The powder was mixed with 0.2 wt% of Irganox B561 (BASF SE), and then compounded and extruded into pellets using a CIMP90 extruder under a nitrogen atmosphere.
[0228] The properties of the polyethylene compositions of Examples IE1-IE3 and CE1-CE4 are listed in Table 2 below.
[0229] Table 2: Properties of polyethylene compositions of IE1-IE3 and CE1-CE4
[0230]
[0231]
[0232] Additionally, the lamellar thickness of the compositions of Examples IE1-IE3 and CE1-CE4 was measured by sequential self-nucleation and annealing (SSA) thermal grading as described above.
[0233] The DSC melting curves of samples processed by the SSA protocol are unique for each ethylene terpolymer material: a function of the catalyst, polymerization process / conditions, comonomer type, and comonomer content. By increasing the amount of comonomer and / or distributing the comonomer more evenly along the polymer chain, the melting peak area at higher temperatures decreases.
[0234] Depending on the amount of material that melts in different temperature ranges, differences between the short-chain branching distributions can be identified.
[0235] The amounts of the fractions of different lamellar thicknesses of the polyethylene compositions of Examples IE1-IE3 and CE1-CE4 are summarized in Table 3. Therein, the fractions of different lamellar thicknesses are divided into the following groups in the columns from left to right:
[0236] The fraction with a lamellar thickness not exceeding 6.1 nm (≤ 6.1 nm),
[0237] A fraction having a lamellar thickness of greater than 6.1 nm to 8.1 nm (>6.1 to ≤8.1 nm),
[0238] The lamellar thickness is a fraction greater than 8.1 nm to 11.8 nm (>5.0 to ≤11.8 nm),
[0239] a fraction having a lamellar thickness of greater than 11.8 nm to 21.7 nm (>11.8 to ≤21.7 nm), and
[0240] The fraction with lamellar thickness greater than 21.7 nm (>21.7 nm).
[0241] Table 3: Content of fractions with different lamellar thicknesses (wt%)
[0242] Fraction CE1 CE2 CE3 IE1 IE2 IE3 CE4 ≤6.1nm 30.9 31.7 31.5 40.6 40.9 36.6 30.7 >6.1 to ≤8.1nm 11.4 10.2 9.5 20.0 20.2 19.7 7.5 >8.1 to ≤11.8nm 15.8 14.6 13.8 29.2 26.4 30.9 11.9 >11.8 to ≤21.7nm 41.9 43.5 45.2 10.2 12.4 12.8 49.8 >21.7nm 0.1 0.1 0.1 0 0 0 0.1
[0243] Compared to the polyethylene compositions of comparative examples CE1 to CE4, the polyethylene compositions of inventive examples IE1 to IE3 show a significantly higher content of a fraction with a low lamellar thickness ranging from 0 to 11.8.
[0244] 3. Membrane
[0245] Monolayer blown films were produced from the polyethylene compositions of Examples IE1 to IE3 and CE1 to CE4 using a Collins Line monolayer blown film line.
[0246] The die diameter was 150 mm, the die gap was 1.8 mm, and the total film thickness was 40 μm.
[0247] The lower neck height and blow-up ratio (BUR) are 2.5.
[0248] The extrusion conditions and film properties are listed in Table 4.
[0249] All samples were easy to process and showed good bubble stability.
[0250] Table 4: Blown film extrusion conditions and properties of CE1, CE2, IE1 and IE2
[0251]
[0252] The films made from the polymer compositions of the present invention in Examples IE1 to IE3 exhibit an excellent balance of properties in terms of mechanical properties, sealing properties and optical properties.
Claims
1. A polyethylene composition comprising a multimodal terpolymer of ethylene and two different comonomers independently selected from α-olefin comonomers having 4 to 10 carbon atoms, in, The multimodal terpolymer comprises: a first copolymer portion, wherein the first copolymer portion is a copolymer of ethylene and a first comonomer, the first comonomer is 1-butene, and the comonomer content of the first comonomer in the polyethylene composition is 0.4 to 2.0 mol%, based on the total molar content of the monomer units of the polyethylene composition, and a second copolymer portion, the second copolymer portion being a copolymer of ethylene and a second comonomer, the second comonomer being selected from α-olefin comonomers having 4 to 10 carbon atoms, the second comonomer having a different carbon atom weight than the first comonomer; The multimodal terpolymer has a density measured according to ISO 1183 of 910 to less than 915 kg / m 3 , preferably 911.0 to 914.5 kg / m 3 , more preferably 911.5 to 914.0 kg / m 3 ;as well as The polyethylene composition has a melt flow rate MFR2 measured according to ISO 1133 at 190° C. and 2.16 kg of 0.5 to 2.5 g / 10 min, preferably 0.6 to 2.2 g / min, more preferably 0.7 to 2.0 g / 10 min.
2. The polyethylene composition according to claim 1, wherein The second comonomer is 1-hexene. Based on the total molar content of monomer units of the polyethylene composition, the total comonomer content of the polyethylene composition is 2.4 to 6.0 mol%, preferably 2.7 to 5.0 mol%, and more preferably 3.0 to 4.5 mol%.
3. The polyethylene composition according to claim 1 or 2, wherein The comonomer content of the first comonomer in the polyethylene composition is 0.5 to 1.5 mol%, preferably 0.6 to 1.2 mol%, based on the total molar content of the monomer units of the polyethylene composition.
4. A polyethylene composition according to any one of the preceding claims, wherein The comonomer content of the second comonomer of the polyethylene composition is 2.0 to 4.0 mol%, preferably 2.2 to 3.5 mol%, more preferably 2.4 to 3.3 mol%, based on the total molar content of the monomer units of the polyethylene composition.
5. A polyethylene composition according to any one of the preceding claims, wherein The polyethylene composition has: A melt flow rate MFR5 of 1.5 to 7.0 g / 10 min, measured at 190°C and 5 kg according to ISO 1133, Preferably 1.7 to 6.0 g / 10 min, more preferably 2.0 to 5.0 g / min; and / or Melt flow rate MFR measured according to ISO 1133 at 190°C and 21.6 kg 21 10.0 to 35.0 g / 10 min, preferably 12.5 to 32.5 g / 10 min, more preferably 15.0 to 30.0 g / min; and / or Flow rate ratio FRR 21 / 2 is 15.0 to 25.0, preferably 16.5 to 23.5, more preferably 17.5 to 22.5, the flow rate ratio FRR 21 / 2 MFR 21 ratio to MFR2; and / or Flow rate ratio FRR 21 / 5 is 4.5 to 10.0, preferably 5.5 to 9.0, more preferably 6.0 to 8.0, the flow rate ratio FRR 21 / 5 MFR 21 Ratio to MFR5.
6. A polyethylene composition according to any one of the preceding claims, wherein The polyethylene composition has a polydispersity index of 2.0 to 6.0, preferably 2.5 to 5.5, wherein the polydispersity index is the ratio of weight average molecular weight to number average molecular weight, Mw / Mn.
7. A polyethylene composition according to any one of the preceding claims, wherein The polyethylene composition has: a melting temperature determined by DSC measurement of 120 to 130°C, preferably 123 to 128°C; and / or a melting enthalpy determined by DSC measurement of 100 to 115 J / g, preferably 103 to 110 J / g, and / or a degree of crystallinity determined by DSC measurement of 30% to 40%, preferably 35% to 38%.
8. A polyethylene composition according to any one of the preceding claims, wherein The polyethylene composition has a molecular structure comprising fractions of different lamellar thicknesses, wherein Based on the total amount of the lamellar fraction, the amount of the fraction having a lamellar thickness of greater than 11.8 nm to 21.7 nm is 5.0 to 25.0%, preferably 7.5 to 22.5%, more preferably 10.0 to 20.0%; and / or Based on the total amount of the lamellar fraction, the amount of the fraction having a lamellar thickness of greater than 8.1 nm to 11.8 nm is 17.5 to 40.0%, preferably 20.0 to 37.5%, more preferably 22.5 to 35.0%; and / or Based on the total amount of the lamellar fraction, the amount of the fraction having a lamellar thickness of greater than 6.1 nm to 8.1 nm is 12.5 to 30.0%, preferably 15.0 to 27.5%, more preferably 17.5 to 25.0%; and / or The amount of the fraction having a lamellar thickness of 0 nm to 6.1 nm is 30.0 to 50.0%, preferably 32.5 to 47.5%, more preferably 35.0 to 45.0%, based on the total amount of the lamellar fraction; Therein, the amount of fractions with different lamellar thicknesses is determined by successive self-nucleation and annealing SSA thermal fractionation.
9. A method for producing a polyethylene composition according to any one of the preceding claims, wherein: Both the first copolymer portion and the second copolymer portion are polymerized in different polymerization reactors of a multi-stage polymerization process in the presence of a single site catalyst.
10. The method according to claim 9, comprising the steps of: a) polymerizing ethylene and a first comonomer in the presence of a single site catalyst in a first polymerization reactor to obtain a first reaction mixture comprising a first copolymer portion and the single site catalyst; b) transferring the first reaction mixture from the first polymerization reactor to a second polymerization reactor; c) polymerizing ethylene and a second comonomer in the presence of the single site catalyst and the first copolymer fraction in a second polymerization reactor to obtain a second reaction mixture comprising the first copolymer fraction, the second copolymer fraction, and the single site catalyst; d) removing the second reaction mixture from the second polymerization reactor; and e) compounding the second reaction mixture to obtain a polyethylene composition.
11. The method according to claims 9 and 10, wherein: The molar ratio of the first comonomer used for the polymerization of the first copolymer portion to ethylene is greater than 110 mol / kmol to 350 mol / kmol, preferably 125 mol / kmol to 300 mol / kmol, more preferably 150 to 275 mol / kmol, and / or the molar ratio of the second comonomer used for the polymerization of the second copolymer portion to ethylene is 15 mol / kmol to less than 41 mol / kmol, preferably 17 mol / kmol to 40 mol / kmol, more preferably 20 to 30 mol / kmol.
12. An article, preferably a film, comprising the polyethylene composition of any one of the preceding claims.
13. The article according to claim 12, which is a film, the film having: The dart drop impact strength DDI measured according to ISO 7765-1, method A on a single-layer blown film with a thickness of 40 μm is at least 1000 g, preferably at least 1100 g, more preferably at least 1200 g; and / or A hot stick temperature at a maximum force of 1 N, measured according to ASTM F 1921 on a single-layer blown film having a thickness of 40 μm, of 65 to 90° C., preferably 70 to 88° C., more preferably 75 to 85° C.; and / or The gloss at 60°, measured according to ISO 2813 on a monolayer blown film with a thickness of 40 μm, is 20 to 50.
14. The article according to claim 12 or 13, wherein The article is a monolayer film, a layer of a multilayer film for flexible packaging, a collation shrink film or a heavy duty shipping bag.
15. Use of the polyethylene composition of any one of claims 1 to 11 for the manufacture of an article, preferably a film, more preferably a monolayer film, a layer of a multilayer film for flexible packaging, a collation shrink film or a heavy-duty transport bag.
Citation Information
Patent Citations
Closed loop recycle of vent gas in polymerization process
EP0188125A2
Fluidised bed discharge device
EP0250169A2
Apparatus and method for producing ethylene polymer
EP0479186A2
Polymerization process
EP0579426A1
Process for polymerizing monomers in fluidized beds
EP0696293A1